INOVASI PRODUK NANAS DAN DAUN SINGKONG BERBASIS EKONOMI KREATIF MELALUI DIGITALISASI PEMASARAN DI DESA PRINGGASELA - Janah, Qanita Izzatul; Suharni, Suharni; Khaerunnisa, Erma; Kurniawan, Lalu Wahyudi; Zulqarami, Hilman; Hidayat, Hamzah Fansuri; Maulida, Luthfiyah; Kamiliani, Cahya; Asfahunnisah, Asfahunnisah; Kusuma, L.M. Septa Hadi; Buana Sakti, Dwi Putra (Universitas Mataram, 2025)
Pringgasela Village possesses abundant agricultural potential, particularly in pineapples and cassava crops. However, the utilization of these agricultural products remains limited due to a lack of processing innovation, access to modern technology, and effective marketing strategies. The Community Empowerment Field Study Program (KKN-PMD) of Universitas Mataram 2024-2025 aims to enhance the added value of these agricultural products through product innovation and the digitalization of marketing based on the creative economy. The innovations implemented include processing pineapples into syrup and jam, as well as transforming cassava leaves into chips. In addition, the program encompasses community outreach and digital marketing training to broaden the market reach of local products. The methods employed consist of observation, interviews, product development, and digital marketing training using the Participatory Rural Appraisal (PRA) approach. The results indicate that product innovation and digital marketing strategies have a positive impact on increasing community understanding of product processing and technology-based marketing. With this program, it is expected that the community will become more self-reliant in developing businesses based on local potential, thereby enhancing the village’s economic welfare.